1-FFT amino acids involved in high DP inulin accumulation in Viguiera discolor - De Sadeleer, Emerik; Struyf, Tom; Vergauwen, Rudy; Le Roy, Katrien; Van den Ende, Wim (Frontiers in Plant Science, 2015)
Fructans are important vacuolar reserve carbohydrates with drought, cold, ROS and general abiotic stress mediating properties. They occur in 15% of all flowering plants and are believed to display health benefits as a prebiotic and dietary fiber. Fructans are synthesized by specific fructosyltransferases and classified based on the linkage type between fructosyl units. Inulins, one of these fructan types with β(2-1) linkages, are elongated by fructan:fructan 1-fructosyltransferases (1-FFT) using a fructosyl unit from a donor inulin to elongate the acceptor inulin molecule. The sequence identity of the 1-FFT of Viguiera discolor (Vd) and Helianthus tuberosus (Ht) is 91% although these enzymes produce distinct fructans. The Vd 1-FFT produces high degree of polymerization (DP) inulins by preferring the elongation of long chain inulins, in contrast to the Ht 1-FFT which prefers small molecules (DP3 or 4) as acceptor. Since higher DP inulins have interesting properties for industrial, food and medical applications, we report here on the influence of two amino acids on the high DP inulin production capacity of the Vd 1-FFT. Introducing the M19F and H308T mutations in the active site of the Vd 1-FFT greatly reduces its capacity to produce high DP inulin molecules. Both amino acids can be considered important to this capacity, although the double mutation had a much higher impact than the single mutations.